Skala zjawiska wykorzystywania rachunkowości zarządczej w bankach spółdzielczych w Polsce - Siudek, Tomasz (The scope of applying management accounting in cooperative banks in Poland, 2006)
In this paper, the author has determined an impact of selected variables, namely: the level of own funds and total assets in the cooperative banks, the type of banks’ association, the numer and the type of communes as well as regions of their activity, and additionally the level of the ROA, on the use of the management accountancy in the cooperative banks in Poland. Research results indicate that no more than the region of the cooperative banks’ activity has had significant impact on the level of use of management accounting in the process of decision-making in the banks under consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 375-382